2011
DOI: 10.3382/ps.2010-01185
|View full text |Cite
|
Sign up to set email alerts
|

Functional and rheological properties of proteins in frozen turkey breast meat with different ultimate pH

Abstract: Functional and rheological properties of proteins from frozen turkey breast meat with different ultimate pH at 24 h postmortem (pH(24)) have been studied. Sixteen breast fillets from Hybrid Tom turkeys were initially selected based on lightness (L*) values for each color group (pale, normal, and dark), with a total of 48 breast fillets. Further selection of 8 breast samples was made within each class of meat according to the pH(24). The average L* and pH values of the samples were within the following range: p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 51 publications
2
36
0
Order By: Relevance
“…Decreased hardness of meat gels exhibited the soft characteristics of the PSE-like meat. However, no significant differences were observed in other textural parameters between two color groups in broilers and in the cohesiveness in turkeys (Chan et al, 2011c). The inconsistent results were probably due to the samples selection, or the method of meat batters preparation and cooking conditions.…”
Section: Chemical Composition Of Normal and Pse-like Chicken Breast Meatmentioning
confidence: 65%
See 1 more Smart Citation
“…Decreased hardness of meat gels exhibited the soft characteristics of the PSE-like meat. However, no significant differences were observed in other textural parameters between two color groups in broilers and in the cohesiveness in turkeys (Chan et al, 2011c). The inconsistent results were probably due to the samples selection, or the method of meat batters preparation and cooking conditions.…”
Section: Chemical Composition Of Normal and Pse-like Chicken Breast Meatmentioning
confidence: 65%
“…There was no significant difference in the textural characteristics between normal and PSE-like turkey meat batters (Chan, Omana, & Betti, 2011b). However, Chan, Omana, and Betti (2011c) have compared the functional properties of PSE-like and normal turkey *Corresponding author. Email: xlxu@njau.edu.cn CyTA -Journal of Food, 2015Vol.…”
Section: Introductionmentioning
confidence: 99%
“…Chan et al (2011) examined the functional and rheological properties of proteins in frozen Turkey breast meat and reported that in terms of dynamic viscoelastic 1 behavior, low, normal, and high pH meat had the same myosin denaturation temperature (Chan et al 2011). For example, Álvarez et al (2012) carried out a study on textural and viscoelastic properties of pork frankfurters containing canolaolive oils, rice bran, and walnut (Álvarez et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, emulsifying capacity of myofibrillar protein was not affected by probiotic feeding levels under cyclic heat challenge (Table 5). In addition, Chan et al (2011) found that pH of poultry breast muscle mostly affected emulsifying capacity of sarcoplasmic protein, but not that of myofibrillar protein. This could elucidate no direct effects of probiotic supplementation on WHC of either intact or ground breast muscles from chickens exposed to cyclic heat challenge, in that myofibrillar proteins are largely associated with muscle pro-tein functionalities, rather than sarcoplasmic proteins (Xiong and Brekke, 1989;Wang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%